THE EFFECTIVENESS OF DAYAK ONION BULBS EXTRACT (ELEUTHERINE PALMIFOLIA (L) MERR.) AGAINST ROOT CANAL MIXED BACTERIAL (Preface Study As Root Canal Irrigation Materials) - Ratih Yusnita; Muhammad Yanuar Ichrom Nahzi; Sherli Diana (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Dayak onion (Eleutherine palmifolia (L) Merr) is a native plant from Central Kalimantan and has been trusted as a multifunctional plant, one of them is as an antibacterial. Purpose: To find out the difference in the effectiveness of Dayak onion bulbs extract with various concentrations on the growth of mixed bacterial of root canal to be used as an alternative root canal irrigation. Methods: This study used true experimental research design namely post-test only with control group design treated with 5 different treatments, Dayak onion bulbs extract at concentrations of 20 mg/ml, 40 mg/ml, 60 mg/ml, 80 mg/ml and 5,25% sodium hypochlorite, and done with 5 times repetitions. The antibacterial effect test was performed using diffusion method. Result: The result of  average diameter of inhibition zone formed on Dayak onion bulbs extract at concentrations of 20 mg / ml, 40 mg / ml, 60 mg / ml, 80 mg / ml and 5.25% sodium hypochlorite to the root canal mixed bacterial in sequence i.e. 12.74 mm , 15.82 mm, 20.38 mm, 25.90 mm and 23.52 mm. One Way Anova Test result and Post Hoc LSD test obtained the value p=0,000 (p<0,05). It proved that there were difference of antibacterial activity of Dayak onion bulbs extract concentration 20 mg/ml, 40 mg/ml, 60 mg/ml, 80 mg/ml and sodium hypochlorite 5,25% against mixed bacteria of the root canal. Conclusion: Dayak onion bulbs extract with concentration of 80 mg/ml has greatest antibacterial activity to inhibit the growth of root canal mixed bacterial.